2010
DOI: 10.1097/phh.0b013e3181e31d09
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Housing Interventions and Health

Abstract: Subject matter experts systematically reviewed evidence on the effectiveness of specific housing interventions in improving health. The panelists reviewed housing interventions associated with exposure to biological and chemical agents, structural injury hazards, and community-level interventions. Intervention studies were grouped together according to recommendations in the Guide to Community Preventive Services, which identifies similarities in the type of intervention, its delivery and setting, and the targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
48
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…The reviews identified 34 interventions of unknown or inconclusive health effects and 7 that were potentially ineffective. 24 Neighborhood-level interventions such as demolishing and revitalizing poor public housing (e.g., HOPE VI 37 ), relocating residents, and various forms of neighborhood redesign yielded too little evidence to draw conclusions. 28 Some commentators have emphasized the social harms linked to housing clearance and demolition programs.…”
mentioning
confidence: 99%
“…The reviews identified 34 interventions of unknown or inconclusive health effects and 7 that were potentially ineffective. 24 Neighborhood-level interventions such as demolishing and revitalizing poor public housing (e.g., HOPE VI 37 ), relocating residents, and various forms of neighborhood redesign yielded too little evidence to draw conclusions. 28 Some commentators have emphasized the social harms linked to housing clearance and demolition programs.…”
mentioning
confidence: 99%
“…5 Physical, chemical, and biological exposures in the home that produce adverse health outcomes and associated housing interventions have been reviewed elsewhere. [6][7][8][9] Data are needed to elucidate the complex links between health, buildings, and communities to enable building owners, community planners, and others to more confidently implement health-based housing interventions. This study sought to determine whether renovating low-income housing using green and healthy principles improved resident health and building performance.…”
mentioning
confidence: 99%
“…A number of systematic reviews have recently also explored the range of positive outcomes from residential energy retrofit programmes (Thomson et al, 2004(Thomson et al, , 2009(Thomson et al, , 2013Jacobs et al, 2010). Indeed the idea of co-benefits of energy policy for health, including the possibility of both intended and unintended consequences, has generated extensive research and policy interest in many disciplines over the last decade (Howden-Chapman and Chapman, 2012;Howden-Chapman and Preval, 2014;Woodward, 2014).…”
mentioning
confidence: 98%